Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Elevating Education at High Altitude: EdTech implementation in Gilgit-Baltistan - Aslam, M. Nawaz; Mazari, Haani; Hayat, Amal; Hassan, Syed Mustafa; Afzal, Nimra; Zahir, Jazib; Ministry of Federal Education and Professional Training, Pakistan (EdTech Hub, 2024)
Gilgit-Baltistan, located in the northernmost part of Pakistan, is a region known for its mountainous geography. Its complex geography creates challenges for education, such as geographic isolation and infrastructural limitations. While technology offers the potential to overcome these barriers of isolation, several infrastructural and capacity barriers prevent equitable access to EdTech. The Government of Gilgit-Baltistan has strived to respond to these barriers by introducing a more holistic EdTech implementation model that aims to contextualise solutions toward infrastructural and capacity needs. The study investigates the government’s reforms and initiatives to identify good practices and provide further recommendations to enhance EdTech implementation in Gilgit-Baltistan. It also considers the strengths and opportunities that shape Gilgit-Baltistan’s approaches to implementing EdTech through the 'STEAM' and 'Smart Schools' interventions. Key elements of the government’s approach to implementing EdTech include a focus on aligning intervention design with infrastructural needs, for example, by considering solarisation to improve access to power sources. The introduction of ‘hot spots’ to enable offline access to an LMS has enabled schools to access preloaded, curriculum-aligned teaching and learning materials. To overcome challenges in teacher capacity, the government invested in ‘Tech Fellows’ (IT graduates who support teachers with classroom integration) to bridge the gap between limited digital skills and implementation requirements. In this study, we find areas through which this model can be strengthened and highlight examples that implementers in low-resource settings can learn from. low-resource contexts; blended learning; Pakistan; Gilgit-Baltistan; digital skills; teacher training; solar energy; offline solutions An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence